Funny face [videorecording (DVD)] - Donen, Stanley; Hepburn, Audrey, 1929-1993; Thompson, Kay, 1909-1998; Lee, Ruta, 1936-; Astaire, Fred; Gershwin, George, 1898-1937; Gershwin, Ira, 1896-1983 (Paramount Home Entertainment, 2011)
A young fashion photographer falls in love with a drab bookseller in this musical.